Revision of the malagassy endemic genus Amberana Distant (Hemiptera, Cercopidae) with description of one new genus - Soulier-Perkins, Adeline; Kunz, Gernot (Zootaxa, 2012)
The genus Amberana Distant is revised. Three new species, A. attei Soulier-Perkins sp. n., A. ouvrardi Soulier-Perkinssp. n. and A. pascali Soulier-Perkins sp. n. are described. Lectotypes are designated for A. dimidiata (Signoret, 1960), A.fissurata Jacobi, 1917, A. noualhieri (Lallemand, 1920), A. sexguttata (Melichar, 1915) and A. uncinata Jacobi, 1917. Am-berana tripunctata var. completa Lallemand, 1949 and A. tripunctata Lallemand, 1920 are synonymised with A. bergevini(Lallemand, 1920). A new genus, Bourgoinrana Soulier-Perkins gen. n., is erected for B. perinetana (Synave, 1957),comb. n. (type species), B. rubescens (Synave, 1957), comb. n. and B. sandrangatensis (Synave, 1957), comb. n. Keysto species of Amberana and Bourgoinrana Soulier-Perkins gen. n. are provided. Drawings of the male genitalia for all species with exception of A. lemuria (Distant, 1908) are included.